Syriac Monasticism in Tur Abdin: A Present-Day Account - DelCogliano, Mark (Cistercian studies quarterly, 2006)
The article focuses on the history of Syriac Orthodox Christianity and its rich monastic life that take root in Tur Abdin, Turkey. The local tradition tells that it was the follower of Thomas, one of the apostles of Jesus Christ, named Addai that had brought Christianity to Edessa of which later has later spread out to the neighboring regions. The birth of the Syriac Orthodox Church has been seen from the 5th Century which believe to be in lineage with the apostolic succession.